Enhancing IT Project Agility Through Effective Change Management Strategies - Zangana, Hewa Majeed; Omar , Marwan; Ali , Natheer Yaseen; Abdullah , Dilovan Taha (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2025)
In the dynamic landscape of Information Technology (IT) projects, agility is paramount for success. This paper explores the critical role of effective change management strategies in enhancing IT project agility. By integrating change management practices with agile methodologies, organizations can better adapt to evolving requirements and unexpected challenges. This study examines key change management principles and their application within agile frameworks, highlighting best practices and case studies that demonstrate successful outcomes. The findings suggest that a proactive and flexible approach to change management not only mitigates risks but also accelerates project delivery and improves stakeholder satisfaction. Ultimately, the synergy between change management and agility can significantly enhance the performance and resilience of IT projects.